Association of fragmented QRS complexes on ECG with left ventricular diastolic function in hypertensive patients - Hasan Kadı; Ayşe Kevser Demir; Köksal Ceyhan; İbrahim Halil Damar; Kayıhan Karaman; Çağrı Zorlu (KARE Publishing, 2015)
Objectives: Diastolic dysfunction occurs as a result of interstitial fibrosis in hypertensive patients. Fragmented QRS (fQRS) on ECG signifies myocardial fibrosis in various clinical situations. We investigated whether fQRS on ECG is related to diastolic dysfunction in patients with hypertension. Study design: The study population included 72 hypertensive patients with normal coronary angiogram. Fragmented QRS was defined as the presence of an additional R wave (R'), notching of the R or S wave or fragmentation in two contiguous leads corresponding to a major coronary artery. Echocardiography was performed to all patients to detect diastolic dysfunction. Diastolic dysfunction was regarded as non-severe if patients had normal diastolic function or grade 1 diastolic dysfunction or severe if they had grade ≥2 diastolic dysfunction. Results: Thirty-two patients had fQRS on ECGs (fQRS [+] group) and there were 40 patients who did not have fQRS on their ECGs (fQRS [-] group). The two groups were similar in terms of baseline characteristics. In patients with fQRS on the ECG, severe diastolic dysfunction was more prevalent (59.4% vs. 7.5%, p<0.001). The duration of hypertension was longer in patients with fQRS on the ECG (p<0.001). The presence of fQRS on the ECG was an indicator for severe diastolic dysfunction (B=1.954; odds ratio=7; 95% confidence interval=1.4-35.4; p=0.018). Conclusion: The presence of fQRS complexes on ECG predicts more severe diastolic dysfunction in patients with hypertension.